Wnt/β-Catenin Pathway Is Regulated by PITX2 Homeodomain Protein and Thus Contributes to the Proliferation of Human Ovarian Adenocarcinoma Cell, SKOV-3 - Basu, Moitri (American Society for Biochemistry and Molecular Biology, 2013)
Pituitary homeobox-2 (PITX2) plays a substantial role in the development of pituitary, heart, and brain. Although the role of PITX2 isoforms in embryonic development has been extensively studied, its possible involvement in regulating the Wnt signaling pathway has not been reported. Because the Wnt pathway is strongly involved in ovarian development and cancer, we focused on the possible association between PITX2 and Wnt pathway in ovarian carcinoma cells. Remarkably, we found that PITX2 interacts and regulates WNT2/5A/9A/6/2B genes of the canonical, noncanonical, or other pathways in the human ovarian cancer cell SKOV-3. Chromatin immunoprecipitation and promoter-reporter assays further indicated the significant association of PITX2 with WNT2 and WNT5A promoters. Detailed study further reveals that the PITX2 isoform specifically activates the canonical Wnt signaling pathway either directly or through Wnt ligands. Thus, the activated Wnt pathway subsequently enhances cell proliferation. Moreover, we found the activation of Wnt pathway reduces the expression of different FZD receptors that limit further Wnt activation, demonstrating the existence of an auto-regulatory feedback loop. In contrast, PITX2 could not activate the noncanonical pathway as the Wnt5A-specific ROR2 receptor does not express in SKOV-3 cells. Collectively, our findings demonstrated that, despite being a target of the canonical Wnt signaling pathway, PITX2 itself induces the same, thus leading to the activation of the cell cycle regulating genes as well as the proliferation of SKOV-3 cells. Collectively, we highlighted that the PITX2 and Wnt pathway exerts a positive feedback regulation, whereas frizzled receptors generate a negative feedback in this pathway. Our findings will help to understand the molecular mechanism of proliferation in ovarian cancer cells.